Tinjauan Atas Pajak Penghasilan Pekerja Lepas (Freelancer) - Khoirunnisa, Luthfiyah; Kusuma, I Gede Komang Chahya Bayu Anta (JURNAL PAJAK INDONESIA, 2024)
This research aims to discuss the Income Tax for Freelancers in the city of Malang. The methods used in this research include literature review and interviews, the collection of data and information from various relevant literature on the research topic, as well as primary data obtained through interviews with informants. The rapid advancement of technology has made it easier for people to work as freelancers from anywhere. In general, there is no withholding tax (Article 21) on commissions earned by freelancers, but freelancers using freelancing platforms such as Upwork will be subject to commission deductions. Freelancers who have earned income above the Non-Taxable Income Threshold (PTKP) or have met the subjective and objective criteria are required to have a Tax Identification Number (NPWP) and fulfill their tax obligations. However, in practice, only a few freelancers are aware of their tax obligations.